RESEARCH ON THE APPLICATION OF PARTICLE DAMPING TUNED MASS DAMPER IN THE LATERAL VIBRATION SUPPRESSION OF 5G COMMUNICATION TOWER - LUO Yuanyi; XIAO Wangqiang; REN Zhixing (Jixie qiangdu)
Single tube towers are widely used as the foundation for carrying 5G communication equipments. Due to construction needs, the mounted equipments often changes with the changes in 5G construction. Due to the small damping of the single tube tower, the increase of mounted equipments may cause an excessive vibration, reducing its load capacity. Therefore, the control of tower top vibration is particularly crucial. A particle damping tuned mass damper (PDTMD) method was proposed to control the problem of excessive vibration at the top of 5G communication towers. Based on a collision theory, a mathematical model using PDTMD to control the vibration of the communication tower was established. The vibration response of the tower under effects of PDTM was verified by the detailed calculation, and the damping mechanism of PDTMD was analyzed. The damping effectiveness of PDTMD was compared with the traditional tuned mass damper (TMD). The results show that the particle damping has good energy dissipation ability. Compared with traditional tuned mass dampers, PDTMD has better damping effect and higher robustness. Finally, based on the actual signal tower, the usage parameters of PDTMD in complex environments were optimized. Effects of gaps between damping particles and honeycomb structures, particle materials, and particle mass ratios on the damping effect of dampers were analyzed.